Enhancing Healthcare Consulting Services: Addressing Accessibility and Quality Challenges in Indonesia - Sadira Ferda Zahira; Reza Eka Lestari (Journal of Transformative Governance and Social Justice, 2025)
The National Health Insurance Program (JKN), implemented by the Social Security Organizing Agency (BPJS) Kesehatan, aims to provide affordable healthcare access for all Indonesian citizens. However, the program faces challenges regarding access and quality of consultation services. BPJS Kesehatan participants often report difficulties obtaining adequate consultation services due to several contributing factors, including a limited number of medical personnel, a complex referral system, and suboptimal utilization of technology. The shortage of medical personnel, particularly doctors, is a significant obstacle. Indonesia’s doctor-to-patient ratio falls far below the WHO standard, leaving healthcare facilities overwhelmed by the growing number of BPJS participants. Additionally, while intended for efficiency, the complex referral system can hinder patient access to specialist doctors. Furthermore, the utilization of technology such as telemedicine remains limited despite its potential to improve access and efficiency in consultation services. These issues surrounding access and quality of consultation services have significant consequences for both BPJS Kesehatan participants and the national health system. Participants facing difficulties accessing essential healthcare services may experience delays in diagnosis and treatment, potentially worsening their health conditions and increasing healthcare costs. This situation can also reduce individual productivity, ultimately burdening the national health system. To address these challenges, comprehensive policy interventions are necessary, such as developing and expanding telemedicine infrastructure, increasing the number of medical personnel, simplifying the referral system, and increasing the budget for BPJS Kesehatan. By addressing the issues of access and quality in consultation services, the JKN program can be more effective in achieving its goal of improving the health of the Indonesian people.